The Influence of Joyful Learning Strategies on Learning Outcomes of Class 3 The History of Islamic Culture MI Nurussalam Mantingan Ngawi' - Heru; Zuhrotul Mufidah; Fatimah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The History of Islamic Culture is a history that happened in the past. Many people need to remember and pay attention to it. Many students need to pay more attention to it because the teacher only does good teaching once students become bored and decrease their academic scores. An example of a strategy is Joyful Learning, this strategy to learn by playing, which creates a pleasant learning atmosphere. Research objectives: to know the influence of Joyful Learning on achieving Islamic Cultural History class 3 MI Nurussalam. The researcher used an experimental method, which is to use a Quasi-Experimental Design. The population in this study was all students in class 3, with a total of 48 samples. Data collection was used to analyze the Mann-Withney test formula with the help of SPSS 16.0. The results obtained with Asymp.Sig (2-tailed) were 0.006 <0.05. There is an influence of Joyful Learning on class 3 MI Nurussalam.' The students; to be more active and enthusiastic in studying Islamic Cultural History because these lessons help them understand the history of the Prophet SAW